Strategi Government Public Relations oleh Dinas Sosial DKI Jakarta (Studi Pada Akun @pusdatinkesosdki Dalam Memberi Sosialisasi Mengenai Data Terpadu Kesejahteraan Sosial (DTKS) - Ghiffari, Faiz (Universitas Al Azhar Indonesia, 2024)
The implementation of Government Public Relations (GPR) in the Integrated Social Welfare Data Program (DTKS) in Petukangan Utara Subdistrict is an important step to increase the effectiveness of the program. DTKS, a government initiative to integrate data on beneficiaries of social welfare programs, aims to ensure that aid is distributed on target. In this context, GPR plays a key role in conveying information, overcoming misperceptions, and encouraging community participation. Delivering clear information through public information campaigns, dialogue forums and mass media is an important strategy in implementing GPR. By establishing partnerships with the media, the government can voice the aspirations of the community while providing accurate information. Training and mentoring are also important in ensuring that the community can make good use of DTKS data.